ASPEK ASPEK TEOLOGIS DAN FILOSOFIS TENTANG WALI DAN SAKSI PERKAWINAN - Nasution, Ali Sahban (Program Studi Hukum Keluarga Islam Universitas Islam Negeri Raden Intan Lampung, 2020)
Abstract: Theological and Philosophical Aspects of Marriage Guardians and Witnesses. In carrying out marriage in Islam it teaches that there are conditions and harmonious conditions that must be considered so that the marriage is in accordance with the will of Allah SWT. One of the conditions in marriage is Guardian and Witness, the discussion about Guardians and Witnesses is not something new in the world of family law, it is often analyzed and studied, but in reality there are still many in the midst of society who wrongly interpret the wisdom behind the existence of Guardians and Witnesses, This needs to be reexamined so that the lack of understanding can be minimized, this problem is what the writer wants to contribute to writing about the meaning and wisdom of guardians and witnesses in marriage, so that to explore this the writer uses theological and philosophical approaches. In this paper the authors conclude that the Theological Aspect The existence of a guardian is one of the pillars for the validity of a marriage, in addition to the husband, wife, guardian, two witnesses and consent granted. The appointment of a guardian as one of the pillars of the validity of the marriage does not want to complicate the implementation of the marriage, but is based on a number of valid texts. Furthermore, the philosophical aspect of having a guardian in a marriage is a form of legal agreement from the female guardian that he will build a household with a man who will marry his own guardian, as well as a form of the validity of the relationship between the man and woman so that the child born from the marriage can be recognized by both sides of their respective families. Furthermore, the theological aspect of witnesses in marriage is one of the conditions for the validity of marriage, without witnesses the marriage is rejected. The philosophical aspect of the presence of witnesses is to avoid slander and tuhmah (bad assumptions), such as cohabitation. The presence of witnesses in a marriage is an agent of i'lan (announcement or notification) to the community about the marriage.Keywords: Theological, Philosophical, Guardian, Witness.